1971
DOI: 10.1159/000178246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Adrenocorticotrophic Effect of a Synthetic Depot Corticotrophin in Normal, Dexamethasone-Blocked, and Hypophysectomised Rats

Abstract: The ACTH stimulation test for depot preparations was carried out with a synthetic depot corticotrophin (Synacthen Depot®) in normal, dexamethasone-blocked, and hypophysectomised rats. It was found that the response curves (plasma and adrenal corticosterone) were very similar in all three groups, the peak values being somewhat higher in the normal and block dexamethasone-blocked animals. Towards the end of the stimulation test, the normal animals showed a marked deviation from the nycterohemeral rhythm. This ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, similar results can be obtained with a single injection of depot ACTH (5 IU or 500^g/kg), given 24 hr before the drug. Barthe and Desaulles (1971) found that the plasma concentrations of corticosterone in rats given 300 µg/kg of depot ACTH s.c reach a peak between 16 to 24 hr. Thus, the protection offered by ACTH against drug overdosage coincides with maximal corticosterone secretion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, similar results can be obtained with a single injection of depot ACTH (5 IU or 500^g/kg), given 24 hr before the drug. Barthe and Desaulles (1971) found that the plasma concentrations of corticosterone in rats given 300 µg/kg of depot ACTH s.c reach a peak between 16 to 24 hr. Thus, the protection offered by ACTH against drug overdosage coincides with maximal corticosterone secretion.…”
Section: Discussionmentioning
confidence: 96%
“…It is preferred, especially in clinical medicine, because it rarely causes adverse, allergic reactions commonly seen after the use of the complete ACTH molecule. A further step in the chemical technology of ACTH was the preparation of depot forms (e.g., hormone adsorbed to a zinc hydrophosphate complex) (Besser et al, 1967; Barthe & Desaulles, 1971). Since crystalline ACTH has a very short half-life (partly due to inactivation at the site of injection), repeated administrations or constant infusion are essential to maintain significant adrenocortical stimulation (Dixon, 1964;László et al, 1970;Matsuyama et al, 1972).…”
Section: A Acth and Corticoidsmentioning
confidence: 99%